The Production and Motivation Mechanism of Sports Cultural Memory Space in Urban Greenway - Qinhui Feng; Weiqiang Wang; Maalla Allam (E3S Web of Conferences, 2021)
To study the relationship between urban greenway cycling space perception and cycling behavior intention, factor analysis, correlation analysis, and regression analysis were used to conduct a questionnaire survey of 411 college students to discover the advantages and disadvantages of urban greenway cycling factor, to achieve the comparison of related indicators and dimensions. The results show that the dimensions of Guangdong urban greenway sports space perception include accessibility perception, supporting perception, service perception, and environmental spatial characteristics; Guangdong college students’ greenway cycling space perception is highly correlated with cycling behavior intention, and there is a positive correlation. Among them, the environmental spatial characteristics are the most influential factors. Greenway accessibility, supporting services, cycling landscapes, etc. can stimulate college students’ greenway cycling behavior intentions. Improving the perception of urban greenway cycling space is an effective strategy to improve college students’ greenway sports behaviour and greenway cycling behaviour.